Methodology for Estimatiom of Logistics Risks and Reliability in Cargo Delivery - O. G. Drozdovskaya (Наука и техника)
Reliability in delivery and risks arising in the process of cargo delivery can be estimated with the help of the presented index system. The offered methods for assigning a level of planned reliability in delivery and level of reliability in delivery of some material flow permit to carry out control and regulate reliability in delivery.